Plasma Humanin and Non-Coding RNAs as Biomarkers of Endothelial Dysfunction in Rheumatoid Arthritis: A Pilot Study - Coradduzza, Donatella; Cruciani, Sara; Di Lorenzo, Biagio; De Miglio, Maria Rosaria; Zinellu, Angelo; Maioli, Margherita; Medici, Serenella; Erre, Gian Luca; Carru, Ciriaco (Non-coding RNA, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disorder associated with an increased risk of cardiovascular disease (CVD), largely driven by peripheral endothelial dysfunction (ED). Humanin, a mitochondrial-derived peptide, has been suggested to play a protective role in endothelial function. However, the relationship between Humanin levels and ED in RA, as well as the interaction between Humanin and non-coding RNAs such as Long Non-Coding RNA GAS5, microRNA-21 (miR-21), and microRNA-103 (miR-103), remains unclear. Objective: This study aimed to investigate the relationship between circulating Humanin levels, non-coding RNAs (GAS5, miR-21, miR-103), and endothelial dysfunction (ED) in patients with RA. Additionally, we explored the correlation between Humanin expression and specific non-coding RNAs (GAS5, miR-21, and miR-103) to better understand their potential role in vascular health. Methods: Peripheral ED was assessed using flow-mediated pulse amplitude tonometry, with Ln-RHI values <0.51 indicating dysfunction. Humanin levels, GAS5, miR-21, and miR-103 were measured in RA patients. Univariate and multivariate analyses were conducted to determine the relationship between these biomarkers and ED. Kaplan–Meier survival analysis and ROC curve analysis were used to assess the prognostic value of Humanin. Results: Higher Humanin levels were significantly associated with better endothelial function (OR = 0.9774, p = 0.0196). Kaplan–Meier analysis demonstrated that higher Humanin levels correlated with improved survival (p < 0.0001). The non-coding RNAs (GAS5, miR-21, and miR-103) did not show significant associations with ED. Conclusions: Humanin is a potential protective biomarker for endothelial dysfunction and survival in RA patients. Further research is needed to explore the interaction between Humanin and non-coding RNAs in the context of vascular health.